A new image encryption algorithm for color medical images - Jin, Danyang (SPIE, 2023)
Recently, telemedicine diagnosis via the Internet has been widely used. The transmission of patients' private data over the network is subject to threats such as tampering, forgery and theft, and unauthorized theft and modification of others' data can cause great distress to patients and physicians. To protect the security of medical images. In this paper, a new encryption method for color medical images is proposed. The method uses 5th order orthogonal Latin square based encoding, DNA arithmetic and zigzag ordering to dislocate and diffuse the images. Its security is tested in terms of correlation coefficient, key sensitivity and noise attacks. The results show that the method has a high level of encryption for color images, can achieve lossless decryption, and outperforms existing methods.